Xanthones with Potential Anti-Inflammatory and Anti-HIV Effects from the Stems and Leaves of Cratoxylum cochinchinense - Yong Zhang; Jia-Ming Guo; Ming-Ming Zhang; Ran Wang; Chai-Huan Liang; Yi-Meng Zhao; Ya-Yuan Deng; Yan-Ping Liu; Yan-Hui Fu (Molecules, 2023)
Four new xanthones, cratocochinones A–D (1–4), together with eight known analogues (5–12), were isolated from the stems and leaves of Cratoxylum cochinchinense. The chemical structures of cratocochinones A–D (1–4) were elucidated by comprehensive spectroscopic analyses and the known compounds were identified by comparisons with the spectral data reported in the literature. All isolated compounds 1–12 were evaluated for their anti-inflammatory activities and anti-HIV-1 activities. Compounds 1–12 showed remarkable inhibitory activities on nitric oxide (NO) production induced by lipopolysaccharide in mouse macrophage RAW 264.7 cells in vitro, with IC50 values in the range of 0.86 ± 0.05 to 18.36 ± 0.21 µM. Meanwhile, compounds 1–12 exhibited significant anti-HIV-1 activities with EC50 which ranged from 0.22 to 11.23 µM. These findings indicate that the discoveries of these xanthones, isolated from the stems and leaves of C. cochinchinense, showing significant anti-inflammatory and anti-HIV-1 effects could be of great importance to the research and development of new natural anti-inflammatory and anti-HIV agents.